Implementation of Predict Observe Explain Model and Outdoor Guided Inquiry in Improving Students' Critical Thinking in Science Learning (Universitas Negeri Semarang, 2019)
This study aims to analyze the implementation of Predict Observe Explain (POE) learning models for increasing critical thinking skills of fifth grade elementary school students, analyze the Implementation of Outdoor Guided Inquiry learning models in increasing critical thinking skills of fifth grade elementary school students, comparing the effectiveness of POE learning model and Outdoor Guided Inquiry in the critical thinking ability of fifth grade elementary school students. This research used a quasi-experiment with pre-test and post-test control group design. The population and sample taken in this study were all fifth-grade students of SD Negeri 1 Sambong (eksperimen group) and SD Negeri 3 Sambong (control group), totaling 42 students. The experimental group was intervened by Outdoor Guided Inquiry while the control group by Predict Observe Explain. In this study data were taken using test instrument and questionners. Data analysis techniques used in this study were independent samples t-test, and classical completeness test and N-gain test. N-gain calculation results show that the average in the OGI class is 0.61, and the POE class is 0.38, which means that the Outdoor Guided Inquiry model is better in improving students' critical thinking abilitis compared to the Predict Observe Explain model. Based on the t-test calculation of OGY and POE classes, ttable = 2.021 and tvalue = 4.265, so tvalue > ttable shows that the OGI learning model is significantly better than the POE model.